Seismic Efficiency for Simple Crater Formation in the Martian Top Crust Analog - Rajšić, Andrea; Miljkovic, Katarina; Collins, G.S.; Wünnemann, K.; Daubar, I.J.; Wójcicka, N.; Wieczorek, M.A. (AMER GEOPHYSICAL UNION, 2021)
The first seismometer operating on the surface of another planet was deployed by the NASA InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission to Mars. It gives us an opportunity to investigate the seismicity of Mars, including any seismic activity caused by small meteorite bombardment. Detectability of impact generated seismic signals is closely related to the seismic efficiency, defined as the fraction of the impactor's kinetic energy transferred into the seismic energy in a target medium. This work investigated the seismic efficiency of the Martian near surface associated with small meteorite impacts on Mars. We used the iSALE-2D (Impact-Simplified Arbitrary Lagrangian Eulerian) shock physics code to simulate the formation of the meter-size impact craters, and we used a recently formed 1.5 m diameter crater as a case study. The Martian crust was simulated as unfractured nonporous bedrock, fractured bedrock with 25% porosity, and highly porous regolith with 44% and 65% porosity. We used appropriate strength and porosity models defined in previous works, and we identified that the seismic efficiency is very sensitive to the speed of sound and elastic threshold in the target medium. We constrained the value of the impact-related seismic efficiency to be between the order of ∼10-7 to 10-6 for the regolith and ∼10-4 to 10-3 for the bedrock. For new impacts occurring on Mars, this work can help understand the near-surface properties of the Martian crust, and it contributes to the understanding of impact detectability via seismic signals as a function of the target media.